Case Report and Literature Review: Bisphosphonate, Sirolimus, and Atenolol Treatment in a 4-Year-Old Child Diagnosed with Gorham–Stout Disease - Su Jin Park; Jae Won Yoo; Moon Bae Ahn (Pharmaceuticals, 2023)
We report a 4-year-old with Gorham–Stout disease (GSD) who was treated with a combination of bisphosphonate, sirolimus, and atenolol. A previously healthy 4-year-old girl presented with back pain after falling on her back 2 months prior. Thoracolumbar spine X-ray revealed diffuse compression spinal fractures in T9-L2. Magnetic resonance imaging (MRI) confirmed multiple compression fractures at T9-L5 and revealed a paraspinal mass along the T1-L1 level. Based on clinical, radiological, and histopathological findings, Gorham–Stout disease was diagnosed. Treatment with sirolimus (0.5 mg twice daily, 1.6 mg/m2) was initiated and intravenous bisphosphonate (pamidronate, 1 mg/kg for 3 days, total 3 mg/kg every 4 months) was added for back pain; she had immediate improvement in back pain. After 9 months with this treatment, she had a mild increase in paraspinal lymphangiomatosis and aggravation in T9-L5 compression fractures; atenolol was administered. The patient underwent 11 months of combination treatment with bisphosphonate, sirolimus, and atenolol, and MRI showed mild degree of reduction in the paraspinal lesions at L1-L5. The patient is currently in stable condition with no back pain or side effects. The triple combination treatment with bisphosphonate, sirolimus, and atenolol may be helpful in stabilizing the disease course of GSD.